2004
DOI: 10.1007/s11255-004-0861-x
|View full text |Cite
|
Sign up to set email alerts
|

The use of isolated sigmoid colon segment for vaginal replacement in young adults

Abstract: Experience with this group of patients leads us to believe that isolated sigmoid segments provides a cosmetic, self-lubricating neovagina with low rates of failure and revision, and without the need for routine dilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…Mucous discharge was experienced initially by all patients, which decreased thereafter with the use of frequent douching to evacuate the mucous, which was comparable to other series [3,22]. Mucous is a natural lubricant and decreases by time.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Mucous discharge was experienced initially by all patients, which decreased thereafter with the use of frequent douching to evacuate the mucous, which was comparable to other series [3,22]. Mucous is a natural lubricant and decreases by time.…”
Section: Discussionsupporting
confidence: 80%
“…Average operative time was 184 min (160-210). Average hospital stay was 11 days (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
“…The liability for anastomotic stricture can be decreased by selection of a bowel segment of adequate blood supply and length that can be mobilized and pulled easily to the perineum without tension, creation of a large enough space between bladder and rectum and generous anastomosis at the hymenal region. The need for regular vaginal dilatation after sigmoid vaginoplasty was advised by some authors (21) while others did not recommend it (22). When we analyzed our data, we found that all cases with vaginal stenosis were sexually inactive and reluctant to perform self vaginal dilatation .Therefore, we propose that regular postoperative dilatation of the anastomotic site till full sexual activity (once/week at least) is preferred to decrease the incidence of this complication.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, a cosmetic neovagina of adequate size was also obtained among the 3 recurrent cases with previous failed vaginoplasty using skin graft so we suggest the use of sigmoid vaginoplasty in secondary cases although the limited number of this patient`s category in our series. Other studies also reported good cosmetic and functional results of sigmoid vaginoplasty (22,27) whereas other authors reported periumbilical pain during intercourse in 5.6% of patients and considered this pain a disadvantage of this procedure (24). With assessment of the functional outcome among the 9 sexually active patients in our series, none of them complained of this pain whereas good results were obtained as all patients experienced intercourses that were satisfactory for them and for their partners.…”
Section: Discussionmentioning
confidence: 95%
“…However, these procedures involve laparotomy and bowel anastomosis, which are procedures associated with increased morbidity. Furthermore, they are not free of complications and instances of restenosis requiring revision are well described [8,9] . Therefore the decision for the neovaginopasty technique still depends on the surgeon's expertise and preferences.…”
Section: Discussionmentioning
confidence: 99%